ANALISIS PERBANDINGAN MAKNA FII SABILILLAH SEBAGAI MUSTAHIQ ZAKAT ANTARA SAYYID ABU BAKAR ASY-SYATHO DAN YUSUF QARDHAWI - Sutisna Sutisna (Univ Ibn Khaldun Bogor, 2020)
This study discusses the differences of opinion of scholars related to mustahiq zakat, especially regarding faction sabilillah group. There is a difference of opinion between the classical cleric of Sayyid Abu Bakr Asy-Syatho and the contemporary cleric Yusuf Qardhawi. This research uses qualitative approach method and using research method of literature study. The main source of this research is the book of I'anah Ath-Tholibin by Sayyid Abu Bakr Asy-Syatho and the Book of Fiqh Al-Zakat by Yusuf Qardhawi (abolished Hukum Zakat Studi Komparatif mengenai status dan filsafat zakat berdasarkan Qur’an dan Hadis). In the discussion of the meaning of fii sabilillah, the majority of the classical fiqh scholars such as Sayyid Abu Bakr Asy-Syatho narrow the meaning of fii sabilillah as jihad-oriented jihad through physical warfare, while the majority of contemporary fiqh scholars extend the meaning of fii sabilillah by not specializing in jihad affairs, orientate to the extent of jihad through physical warfare